HIV patients’ decision of switching to second-line antiretroviral therapy in India - de Mello-Sampayo, F. (AIDS Care, 2015)
The objective is to examine when patients should switch to second-line antiretroviral therapy (ART) under health uncertainty and in the absence of viral load monitoring. We formalize and solve the therapeutic dilemma about whether or not, and when, to switch a therapy. The model's main value-added consists in the concrete application to patients with HIV in India. In our dynamic stochastic model, health level volatility can be understood as the variation in CD4 count and the trend of health level as increases in CD4 count and, thus, decreases in the incidence of opportunistic infections and mortality. The results of the empirical application suggest that the theoretical model can explain ART treatment switch. Treatment switch depends negatively on the volatility of patients' health, and on trend of health, i.e., the greater the variation in CD4 count and the more CD4 count increase, the fewer treatment switches one expects to occur. Treatment switch also depends negatively on the degree of irreversibility. Under irreversibility, low-risk patients must begin the second-line treatment as soon as possible, which is precisely when the second-line treatment is least valuable. The existence of an option value means that ART first-line regimen may be the better choice when considering lifetime welfare. Conversely, treatment switch depends positively on the discount rate and on the correlation between the patient's health under first- and second-line treatments. This means that treatment switch is likelier to succeed in second-line treatments that are similar to the first-line treatments, implying that a decision-maker should not rely on treatment switch as a risk diversification tool.